Controle da drenagem na fonte e sua compatibilização ao plano municipal de saneamento ambiental de Santa Maria - Roman, Carlos Augusto (2015)
The City Hall of Santa Maria hired the Municipal Plan of Environmental Sanitation of Santa Maria (MPLAENS), in relation to the urban drainage, one of the themes of the Plan. The Ministry of Cities encourages the use of urban drainage practices that include as much approaches with compensatory techniques, as approaches with principle of urban development of low impact. Thus, this research aimed to identify if the (MPLAENS) incorporates proposals focused in the control of drainage in the source and how they are adressed. The study was performed in three steps: initially, it was carried out the analysis of measures of control of the storm water runoff proposed in (MPLAENS), in order to understand in which level were received the precepts of measures of control of the storm water runoff at source (MCS). Afterwards, the feasibility of MCS for the city has been verified, considering the restrictions of each device and the particularities of the urban occupation and the hydrologic group of the soil. To provide subsidy for the future sizing of MCS, it was necessary an intermediate step of determination of hydrologic parameters of sizing, such as, update of the relation intensityduration- frequency (IDF), determination of value of the specific flow of predevelopment (Qpd) and the volume of control (v). Based on definitions of control of the drainage at source, it is possible to affirm that, none of the proposals of MPLAENS for the urban drainage meet the precepts of measures of control at source. From the held observations in this study and the data available, it is possible to state that large extent of the urban perimeter of the city has potential for the use of MCS. The suggestions presented in MPLAENS in relation to drainage consist in the construction of approximately 631 km of drainage networks, besides the construction of approximately 180.000 m³ of anti-DSP deposit, being these distributed within the next twenty years of project of the Plan. For an estimate of deployment of the micro drainage network, the authors of MPLAENS adopted the flow of 6,9 m³.s-1, calculated by the rational method with the use of the following parameters: Runoff coefficient (R) = 0,6; Basin area (B) = 1,5 km²; Time of concentration (tc) = rain duration (t) = 1,63 hours; Time of return (Tr) = 10 years; Intensity of the rain (I) = 27,4 mm.h-1. To obtain the referent value of the intensity of the rain (I), the authors used the Gumbel distribution of the data recorded by Instituto Nacional de Meteorologia (National Institute of Meteorology). The IDF equation updated in this study and the same values of (t) and (Tr) used in MPLAENS, results in a value of (I) = 42,72 mm.h-1 for this intensity, and for the same values of (R) and (B) the result is a flow of 10,69 m³.s-1, value 56 percent higher than the present in MPLAENS. The potential of the municipality for the deployment of MCS became evident through the results of this study, thus, the use of drainage practices in small-scale spread over the whole river basin in order to reproduce or maintain the hydrological conditions of predevelopment presents itself as a positive alternative.